Academic partners see benefit in collaborative training. Issue 33 (20th August 2021) - Enos, Gary
Abstract : Partners in a mental health workforce development initiative in central New York believe greater collaboration among mental health disciplines can help improve quality of care to the underserved while also easing a shortage of clinical professionals in the region. An initiative funded by the federal Health Resources and Services Administration (HRSA) is establishing a multidisciplinary training program designed to improve services for high‐need populations.